Breaking the chains? The effects of training a shelter dog in prison on criminal behavior and recidivism. Issue 4 (2nd October 2022) - Duindam, Hanne M.; Creemers, Hanneke E.; Hoeve, Machteld; Asscher, Jessica J.
Abstract: The effectiveness of Dutch Cell Dogs (DCD), a prison-based dog training program, in reducing criminal behavior and recidivism was assessed in a quasi-experimental study in twelve correctional facilities in the Netherlands ( N  = 241). DCD is a program in which incarcerated offenders train a shelter dog bi-weekly for eight weeks. Results demonstrated that DCD ( n  = 121) did not outperform treatment-as-usual (TAU; n  = 120) in official recidivism outcomes and self-reported criminal behavior. However, subgroups based on age and detainees' functioning responded differently in self-reported criminal behavior. Positive effects were found on self-reported criminal behavior for DCD participants who were older, had lower callous-unemotional traits, or had higher treatment motivation. In conclusion, findings provided initial evidence that subgroups may respond differently to a dog training program, however, more experimental research with larger sample sizes is needed.